Analysis of Leak Testing Planning for Carbon Dioxide Piping Systems in the Development of Carbon Capture, Utilization, and Storage Facilities in the Bintuni Basin - Sentiani, Devi; Yuwono, Akhmad Herman, Professor (UI Scholars Hub, 2025)
Carbon Capture, Utilization, and Storage (CCUS) technologies have become a key strategic response to global efforts to reduce CO2 emissions. This study presents a leak testing strategy designed for a carbon dioxide (CO₂) piping system as part of a Carbon Capture, Utilization, and Storage (CCUS) project in the Bintuni Basin, West Papua, Indonesia. This study aims to ensure the system is properly prepared before commissioning by designing a leak test plan that is both practical and technical, based on ASME B31.3, ASME PCC-2, and API STD 520 Part 1. We conducted the process, which involves identifying the system boundaries, selecting the test medium, determining the test pressure, sizing the pressure relief valves, calculating the exclusion zone, and a qualitative risk assessment. The findings highlight the importance of performing a tightness test using nitrogen gas at 90% of the pipe's design pressure, especially for newly installed sections connected to existing LNG facilities. Based on technical analysis, this study provides a clear and applicable reference for field implementation of leak testing in CCUS projects.